what is the laplace transform of

5/2.e^t-3/2.e^-t

2 answers

L{e^t} = 1/(s-1)
L{e^-t} = 1/(s+a)
L is a linear transform, so

L{5/2.e^t-3/2.e^-t} = 5/2 L{e^t} - 3/2 L{e^-t}
= 5/2 * 1/(s-1) - 3/2 * 1/(s+1)
= (s+4)/(s^2-1)
compute the inverse laplace transform 2S^2+13S+5/(s+3)(s-1)^2
i got 3e^t+5e^t+3e^t, not sure it correct
Similar Questions
    1. answers icon 2 answers
  1. the Laplace transform of e^4t(cos 2t)??please i need help. thanks
    1. answers icon 2 answers
  2. Find the Laplace transform of:f(t) = cos^(2)(2t)
    1. answers icon 3 answers
  3. Correctly identify these boundary types in order of A, B, C.Transform, Convergent, Divergent Transform, Convergent, Divergent
    1. answers icon 1 answer
more similar questions